Peningkatan Kemampuan Mengenal Huruf Melalui Media Alphabet Book Pada Kelompok A - Lukluk Jannatin Nangim; Kusumastuti Kusumastuti; Dita Primashanti Koesmadi (NANAEKE: Indonesian Journal on Early Childhood Education, 2023)
This study aims to: 1) find out how the alphabet book media can improve children's ability to recognize letters in group A at Kindergarten Dharma Wanita 2 Pelang Lor Kedunggalar; 2) to find out whether the alphabet book media can improve the ability to recognize letters in group A children at Kindergarten Dharma Wanita 2 Pelang Lor Kedunggalar. The research used was classroom action research (PTK). The object of this research is the Kindergarten of Dharma Wanita Pelanng-Lor, Ngawi. The subjects of this study were children in group A Kindergarten Darma Wanita 2 Pelang Lor Kedunggalar Ngawi, totaling 11 children consisting of 5 boys and 6 girls. The data collection techniques used were observation, interviews and documentation. The results showed that: 1) the learning process through the alphabet book media can improve the ability to recognize letters in groups in Kindergarten Dharma Wanita 2 Pelanglor. It can be seen in the activities carried out, namely in cycle 1 with the theme of plants, the sub-theme of fruit plants, the activities are children ringing letters of the alphabet, sorting letters, mentioning letter symbols. For cycle 2, the words used are longer, such as the word "s-a-w-o". In this activity, children play according to the rules. in cycle 1 dan 2. 2) improving children's language through playing alphabet book activities in group A Kindergarten Dharma Wanita 2 Pelanglor is shown by the increased results of learning activities from children through the pre-cycle data percentage of 27%, namely 3 children who completed out of a total of 11 children . cycle 1 of 54%, namely 6 children out of a total of 11 children. cycle 2 of 82%, namely 9 children out of a total of 11 children. while children who did not complete as many as 2 children with a percentage of 18%.